A widespread picornavirus affects the hemocytes of the noble pen shell (Pinna nobilis), leading to its immunosuppression - Carella, Francesca; Prado, Patricia; De Vico, Gionata; Palić, Dušan; Villari, Grazia; García-March, José Rafael; Tena-Medialdea, José; Cortés Melendreras, Emilio; Giménez-Casalduero, Francisca; Sigovini, Marco; Aceto, Serena (Frontiers in Veterinary Science, 2023)
The widespread mass mortality of the noble pen shell (Pinna nobilis) has occurred in several Mediterranean countries in the past seven years. Single-stranded RNA viruses affecting immune cells and leading to immune dysfunction have been widely reported in human and animal species. Here, we present data linking P. nobilis mass mortality events (MMEs) to hemocyte picornavirus (PV) infection. This study was performed on 30 specimens from wild and captive populations. We sampled P. nobilis from two regions of Spain, Catalonia [24 animals] and Murcia [two animals]), and one region in Italy (Venice [four animals]). The low number of analyzed specimens was due to the scarcity of remaining individuals in the Mediterranean Sea. In 100% of our samples, ultrastructure revealed the presence of a virus (20 nm diameter) capable of replicating within granulocytes and hyalinocytes, leading to the accumulation of complex vesicles of different dimensions within the cytoplasm. As the PV infection progressed, dead hemocytes, infectious exosomes, and budding of extracellular vesicles were visible, along with endocytic vesicles entering other cells. The THC (total hemocyte count) values observed in both captive (eight animals) (3.5 x 10 4 -1.60 x10 5 ml -1 cells) and wild animals ( 14samples) (1.90-2.42 x10 5 ml -1 cells) were lower than those reported before MMEs. Sequencing of P. nobilis (six animals) hemocyte cDNA libraries revealed the presence of two main sequences of Picornavirales, family Marnaviridae. The highest number of reads belonged to animals that exhibited active replication phases and abundant viral particles from transmission electron microscopy (TEM) observations. These sequences correspond to the genus Sogarnavirus -a picornavirus identified in the marine diatom Chaetoceros tenuissimus (named C. tenuissimus RNA virus type II). Real-time PCR performed on the two most abundant RNA viruses previously identified by in silico analysis revealed positive results only for sequences similar to C. tenuissimus RNA virus. These results may not be conclusively identify picornavirus in noble pen shell hemocytes, therefore, further study is required. Our findings suggest that picornavirus infection likely causes immunosuppression, making individuals prone to opportunistic infections, which is a potential cause for the MMEs observed in the Mediterranean.